كلف الجودة واستراتيجية التوازن مع قيمة الجودة - د. صالح ابراهيم يونس الشعباني (PROSPECTIVE RESEARCHES, 2023)
Good quality concept is usually connected with the value and the use of the production in a parallel way to the price. Because of the great interest to improve quality, the production costs increase notably as apparent and hidden costs. To decide the level of the good quality, it is a must to study and analyze its value from the client's point of view on the one hand and the producer's on the other. Consequently, there must be a strategy which balances the value of the good quality and its cost.